Intraoperative MR imaging: preliminary results with 3 tesla MR system - (:unkn) unknown (SPRINGER-VERLAG WIEN, 2006)
Aim of this study is to present the initial clinical experience with 3 testa intraoperative MR (ioMR). Material and methods. The 3T MRI suite is built adjacent to the neurosurgical operation theatre. The magnet room and the operation theatre are interconnected by a door and both RF-shielded. Before the operation, the magnet (3T Trio, Siemens) and the console rooms are disinfected. Whenever imaging is needed during the operation, the door is opened and the patient is transferred from the operation table to the magnet cradle. Axial, sagittal and/or coronal TSE T2. SE T1 and 3D Flash T1 weighted images (4-6 mm section thickness. I mm interstice gap) are obtained according to the lesion. Total examination time is approximately 10 minutes. Results. Twenty-six patients were examined with ioMR. There were ten female and seven male patients. Lesions were pituitary adenoma in 10, low grade glial tumor in 9, meningioma and high grade glial tumor in 2 each and metastasis, haemangioblastoma and chordoma in one each. Follow-up time was I to 9 months. In 16 patients the first intraoperative examination revealed gross total tumor excision. However. in 10 patients due to tumor remnants surgical intervention was continued and a second examination revealed gross total tumor excision in all. Postoperative routine MR examinations confirmed total tumor excision in all patients. No complication occurred in this series. Conclusion. This small group of patients examined with ioMR demonstrated that the procedure is simple, helpful in achieving gross total tumor excision without complications.
Keywords: 3 tesla; intraoperative MR; magnetic resonance imaging; MAGNETIC-RESONANCE; BRAIN-TUMORS; NEUROSURGERY; EXPERIENCE; SURGERY; RESECTION; GLIOMA; IMPLEMENTATION; GUIDANCE; LESIONS